'Step-by-step' method to conduct applied research in organizational engineering and business management (Método 'paso a paso' para la investigación aplicada en el ámbito de la ingeniería organizacional y la gestión empresarial). Issue 1 (2nd January 2021) - Escobar-Sierra, Manuela; Lara-Valencia, Luis-Augusto; ValenciaDeLara, Pilar
ABSTRACT: The management field needs to develop creative and problem-solving capabilities among students and practitioners. In this context, and after recognizing the research methods as a cognitive process part of decision-making, we propose a step-by-step method to conduct applied research in organizational engineering and business management. With this goal, we first conduct a literature review about research methods in an organizational or business context. Subsequently, we explain the theoretical and empirical process that we followed to construct our step-by-step method. Moreover, finally, we present our 'step-by-step' method for applied research in organizations and businesses. We are convinced that research methods are tools that must serve and support researchers, so in our proposal, we detail the activities that must be conducted by a research student, from an eclectic perspective.